Phosphorus recovery from biofilm-enriched sewage by fluidized bed crystallization of vivianite. Issue 3 (June 2022) - Zhou, Jian; Pan, Yang; Feng, Xin; Huang, Yong; Li, Da-Peng
Abstract: Existing techniques to recover phosphorus as vivianite from urban sewage face difficulties in separating the crystals from the sludge. The present study proposes a new process for the recovery of phosphorus as vivianite crystals through fluidized bed crystallization (FBC) from biofilm-enriched phosphorus solution (up to 179.5 mg·L −1 ). The impacts of process parameters on the phosphorus recovery (PR), the crystallization ratio (CR), and the crystal size were examined. Under optimized conditions, i.e., 140 mg·L −1 phosphorus in the raw water, 15 m·h −1 liquid up-flow velocity, and 5 h hydraulic retention time, a single batch of the FBC reaction could attain a high PR of 95.30% and a high CR of 88.23%. After seven consecutive batches of the FBC reaction, large vivianite crystals (d50 = 270.5 µm) could be obtained. The identity of the collected vivianite crystals was verified by X-ray diffraction (XRD), scanning electron microscopy (SEM-EDS), and X-ray photoelectron spectroscopy (XPS) analysis. The proposed process shows high potential as it can turn urban sewage into a valuable resource from which phosphorus can be efficiently recycled. Graphical Abstract: ga1 Highlights: A new phosphorus recovery process system for the recovery of phosphate from urban sewage. Vivianite crystals with high crystallization rate (88.23%) and phosphorus recovery rate (93.80–95.20%) can be generated. Large vivianite crystals (d50 = 270.5 µm) can be collected by consecutive batches.